KEBIJAKAN UPAH: TANTANGAN DI TENGAH SUASANA KRISIS EKONOMI - Prijono Tjiptoherijanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2003)
The difference in understanding between businessmen and workers on the issue of renumeration has caused demonstrations or strike actions demanding higher pay. According to workers, wage is considered take home pay, while for businessmen take home pay is just part of the emolument paid to workers. While workers attribute low work productivity to the low pay they get, businessmen regard the low wages paid to workers as attributable to the low work productivity. The national workers’ emolument determination board DPPN makes efforts to reduce the bickering over wages between workers and businessmen by calculating the minimum wage, which must be paid to the formner by the latter. Such wage should enable workers live fairly well and should thus enhance work productivity.